Insect-pests Associated with Robinia pseudoacacia in the Agroforestry System in Mid-hill Regions of Himachal Pradesh - Sharma, Ajay; Sood, Anil; Verma, T. D. (Indian Forester, 2008)
Robinia pseudoacacia commonly called ’Black locust’ is an exotic tree which was introduced in the country in the late nineteenth century and the plantations done in Shimla forests did well. It is becoming an important component of agroforestry systems in mid-hill regions, especially in Solan District of Himachal Pradesh. It is valued for leaf fodder, timber and as honeybee flora. Being an exotic tree, it is not having its traditional pests but some insects have been encountered feeding on different parts of this tree. Among them, Chaffer beetles were found to feed profusely on the foliage of this tree and take heavy toll of the leaves. Cyclopelta siccifolia (Hemiptera : Pentatomidae) was recorded to be the major pest associated with this tree. Its nymphs and adults were observed to suck the sap profusely from the stem and branches of the tree. Another pentatomid bug Nezara viridula was found to feed on the leaves of R. pseudoacacia. Bagrada cruciferarum adults were also encountered feeding on the leaves. Some other pests of minor importance were also observed to feed on this tree.